Does the Depth of Gastric Ulceration Influence a Modified Dual Therapy with Amoxicilin and Lansoprazole for Helicobacter pylori-Positive Gastric Ulcer? - Takashi Okai; Koushiro Ohtsubo; Junta Sakai; Hiroyuki Watanabe; Yoshiharu Motoo; Atsuhiro Kawashima; Sawabu Norio (Canadian Journal of Gastroenterology)
PURPOSE: To clarify whether the depth of ulceration evaluated by endoscopic ultrasonography (EUS) influences a modified dual therapy with amoxicillin and lansoprazole for the treatment of Helicobacter pylori-positive patients with gastric ulcer.